Implementasi Peraturan Kepala Badan Pertanahan Nomor 1 Tahun 2010 Tentang Standar Pelayanan Dan Penngaturan Pertanahan Dalam Peningkatan Pelayanan Ganti Nama Sertifikat Hak Atas Tanah - Andrei Wibowo; R. Hamdani Harahap; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to analyze how the implementation of the Regulation of the Head of the Land Agency Number 1 of 2010 concerning Service Standards and Land Regulations in Improving the Service of Changing the Name of Land Rights Certificates and its obstacles. Based on the problems that have been described previously, the researchers used this type of qualitative research to answer the research objectives. The results of the study found that the implementation of the Head of the Land Agency Regulation No. 1 of 2010 concerning Service Standards and Land Regulations in Improving the Service of Changing the Name of Land Rights Certificates from the dimensions of communication and available facilities, has not been utilized optimally. Operational time is limited, so that it becomes an obstacle to carrying out the duties of officers to provide services and coordination between departments is constrained by the fact that related parties are not in the office. The factors that are the obstacles faced, the information provided is still not good, there are still applicants who do not know the touch application, limited operating hours due to the pandemic, the completeness of the files brought by some applicants is not complete, technical problems ranging from internet connection, electricity and system disturbance.